Law, politics, and morality in Judaism - Walzer, Michael (Princeton, N.J. : Princeton University Press, 2006)
Jewish legal and political thought developed in conditions of exile, where Jews had neither a state of their own nor citizenship in any other. What use, then, can this body of thought be today to Jews living in Israel or as emancipated citizens in secular democratic states? Can a culture of exile be adapted to help Jews find ways of being at home politically today? These questions are central in Law, Politics, and Morality in Judaism, a collection of essays by contemporary political theorists, philosophers, and lawyers. --From publisher's description.
1. Obligation : a Jewish jurisprudence of the social order / Robert M. Cover -- 2. Judaism and civil society / Suzanne Last Stone -- 3. Civil society and government / Noam J. Zohar -- 4. Autonomy and modernity / David Biale -- 5. Land and people / David Novak -- 6. Contested boundaries : visions of a shared world / Noam J. Zohar -- 7. Diversity, tolerance, and sovereignty / Menachem Fisch -- 8. Responses to modernity / Adam B. Seligman -- 9. Judaism and cosmopolitanism / David Novak -- 10. Commanded and permitted wars / Michael Walzer -- 11. Prohibited wars / Aviezer Ravitzky -- 12. Judaism and the obligation to die for the state / Geoffrey B. Levy.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Jewish law -- Moral and ethical aspects; Public law (Jewish law); Judaism and state; Law -- Israel -- Jewish influences; Droit juif -- Aspect moral; Judaïsme et État.; RELIGION -- Judaism -- Theology; POLITICAL SCIENCE -- History & Theory; Jewish law -- Moral and ethical aspects; Judaism and state; Law -- Jewish influences; Public law (Jewish law); Israel; Jüdisches Recht; Öffentliches Recht; Judentum; Israel; Joods recht; Politiek; Ethiek